The blue lamp - Clarke, Thomas Ernest Bennett 1907-1989; Dines, Gordon 1911-1982; Mendleson, Anthony 1915-1996; Warner, Jack 1896-1981; Bogarde, Dirk 1921-1999; Flemyng, Robert 1912-1995; Hanley, James Frederick 1892-1942 (Studiocanal Limited, 2016)
"Das Blaulicht eines Polizei-Streifenwagens als Leitmotiv einer dokumentarisch aufgezogenen Spielfilmhandlung von der Arbeit und den menschlichen Konflikten eines jungen englischen Polizisten. Ernsthafter, aus dem üblichen Rahmen fallender Kriminalfilm mit Spannung und Niveau." [filmdienst.de]
Original: Großbritannien 1950
Bildformat 1.37:1
Special features: new locations featurette with film historian Richard Dacre ; London locations stills gallery ; production stills gallery ; BBC Radio 3 The essay: british cinema of the 1940s - The blue lamp audio featurette ; exclusive audio commentary featuring Jan Read & academic Charles Barr
Keywords: Film; DVD-Video